A power-density-enhanced MEMS electrostatic energy harvester with symmetrized high-aspect ratio comb electrodes. (12th June 2019) - Honma, Hiroaki; Tohyama, Yukiya; Mitsuya, Hiroyuki; Hashiguchi, Gen; Fujita, Hiroyuki; Toshiyoshi, Hiroshi
Abstract: In this paper, we experimentally demonstrate a new approach to improve the output power of electrostatic energy harvester with an electret skin. A symmetric three-ports comb-electrode mechanism is used to reduce the binding electrostatic force, thereby allowing a smooth mechanical motion of the suspended electrodes of a high-aspect ratio in a small acceleration range. Given the same device footprint, two energy harvesters having different aspect ratios are prepared to compare the power generation performances. The output power is increased 6.4 times by increasing the aspect-ratio from the 7.1 to 33.3. At the same time, the volumetric power density is also improved from 62.5 μ W cm −3 to 270.2 μ W cm −3 . These results suggest a possibility to further enhance the aspect ratio to shorten the charge time of a large storage capacitor for autonomous internet of things wireless sensor node.